Versatile MOR-based boundary condition independent compact thermal models with multiple heat sources. (August 2018) - Codecasa, Lorenzo; Bornoff, Robin; Dyson, James; d'Alessandro, Vincenzo; Magnani, Alessandro; Rinaldi, Niccolò
Abstract: This paper shows that the connection of MOR-based boundary condition independent (BCI) dynamic compact thermal models (DCTMs) and detailed models of heat transfer problems is not straightforward and is subject to numerical issues. In order to overcome this drawback, a novel definition of MOR-based BCI DCTMs is provided, which makes this connection feasible. As a result, the proposed BCI DCTMs can be connected without limitations to any detailed model of heat transfer problems and/or to any other MOR-based BCI DCTM. Highlights: A versatile MOR method is proposed for extracting and connecting BCI DCTMs of non-conformal cartesian grid. Connection of MOR-based BCI DCTMs is explored with detailed thermal model and other DCTMs. The MOR-based BCI DCTMs preserve the easy connection property of DELPHI-like CTMs while modeling many heat sources. DCTMs outperform standard numerical methods in terms of drastically lower CPU time. Package-on-Package assembly and IGBT power module were considered as realistic case studies.